Hallmarks of NLRP3 inflammasome activation are observed in organotypic hippocampal slice culture. Issue 1 (22nd June 2020) - Hoyle, Christopher; Redondo‐Castro, Elena; Cook, James; Tzeng, Te‐Chen; Allan, Stuart M.; Brough, David; Lemarchand, Eloise
Summary: Microglial inflammation driven by the NACHT, LRR and PYD domain‐containing protein 3 (NLRP3) inflammasome contributes to brain disease and is a therapeutic target. Most mechanistic studies on NLRP3 activation use two‐dimensional pure microglial cell culture systems. Here we studied the activation of the NLRP3 inflammasome in organotypic hippocampal slices, which allowed us to investigate microglial NLRP3 activation in a three‐dimensional, complex tissue architecture. Toll‐like receptor 2 and 4 activation primed microglial inflammasome responses in hippocampal slices by increasing NLRP3 and interleukin‐1 β expression. Nigericin‐induced NLRP3 inflammasome activation was dynamically visualized in microglia through ASC speck formation. Downstream caspase‐1 activation, gasdermin D cleavage, pyroptotic cell death and interleukin‐1 β release were also detected, and these findings were consistent when using different NLRP3 stimuli such as ATP and imiquimod. NLRP3 inflammasome pathway inhibitors were effective in organotypic hippocampal slices. Hence, we have highlighted organotypic hippocampal slice culture as a valuable ex vivo tool to allow the future study of NLRP3 inflammasomes in a representative tissue section, aiding the discovery of further mechanistic insights and drug development. Abstract : We used organotypic hippocampal slices to investigate microglial NLRP3 inflammasome responses in a three‐dimensional, complex environment. Priming of NLRP3 inflammasome responses was observed in microglia, and ASC speck formation was dynamically visualized in hippocampal slices. Activation of NLRP3 in microglia in hippocampal slices led to caspase‐1 activation, gasdermin D cleavage and pyroptosis.